Liquid Gating Meniscus‐Shaped Deformable Magnetoelastic Membranes with Self‐Driven Regulation of Gas/Liquid Release. Issue 3 (2nd December 2021) - Liu, Jing; Xu, Xue; Lei, Yi; Zhang, Mengchuang; Sheng, Zhizhi; Wang, Huimeng; Cao, Min; Zhang, Jian; Hou, Xu
Abstract: Liquid gating membranes have been demonstrated to show unprecedented properties of dynamicity, stability, adaptivity, and stimulus‐responsiveness. Most recently, smart liquid gating membranes have attracted increasing attention to bring some brand‐new properties for real‐world applications, and various environment‐driven systems have been created. Here, a self‐driven system of a smart liquid gating membrane is further developed by designing a new sytem based on a liquid gating magnetoelastic porous membrane with reversible meniscus‐shaped deformations, and it is not subject to the complex gating liquid restriction of magnetorheological fluids. Compared with other systems, this magnetic‐responsive self‐driven system has the advantage that it provides a universal and convenient way to realize active regulation of gas/liquid release. Experiments and theoretical calculations demonstrate the stability, the nonfouling behavior, and the tunability of the system. In addition, this system can be used to perfectly open and close gas transport, and the gating pressure threshold for the liquid release can be reduced under the same conditions. Based on the above capabilities, combined with the fast and 3D contactless operation, it will be of benefit in fields ranging from visible gas/liquid mixture content monitoring and energy‐saving multiphase separation, remote fluid release, and beyond. Abstract : A liquid gating magnetoelastic membrane with meniscus‐shaped deformations actuated by magnetic stimuli is reported to actively regulate gas/liquid release. It introduces a universal and new self‐driven strategy for smart liquid gating membranes, combining fast and contactless operation and nonfouling behavior for energy‐saving multiphase fluid transport and separation, and visible gas/liquid mixture content monitoring.